Tradisi Tegak Rumah pada Masyarakat Penghulu di Desa Lubuk Bedorong Kecamatan Limun Kabupaten Sarolangun - Azmi, Ulul (Jurnal Ilmiah Dikdaya, 2022)
The house for the people of Lubuk BeDrive has a broad meaning both in terms of the shape of the building and the procedure for its establishment, starting from choosing building materials to erecting it. It has meaning and significance for the people of Lubuk Bepus, all of which are hereditary traditions that have meaning both in each room and the tradition of its establishment. . The tradition of upright houses that have many life values for the Penghulu community in Lubuk BeDrive Village is unique in terms of constructing buildings or architecture. Establishing a building in this area is called the term upright house. Traditions related to building houses for the Penghulu community in Lubuk BeDrive, Limun District, Sarolangun Regency have many meanings in life, not only found in the parts of the building in the house, but also in various forms. ceremonial tradition of erecting the building from laying the first stone to erecting the building. The upright tradition of the house that needs to be preserved and maintained. This research method is descriptive qualitative which is analyzed using descriptive statistics. It can be concluded that the traditional procession of the upright house in Lubuk BeDrive begins with site selection, selection of wood pick-up poles, unloading tambun, first chisel, family gathering, tengganai gathering, upright fierce, sitting the village of the Core event, and the tintiang event. This study aims to find out how the upright tradition of the house develops in the community, what values are contained in each procession and contained in every form and part of the house building and what is its effect on the life of the Lubuk BeDrive village community.